Genome-Wide Identification and Low Temperature Responsive Pattern of Actin Depolymerizing Factor (ADF) Gene Family in Wheat (Triticum aestivum L.) - Xu, Ke; Zhao, Yong; Zhao, Sihang; Liu, Haodong; Wang, Weiwei; Zhang, Shuhua; Yang, Xueju (Frontiers in Plant Science, 2021)
The actin depolymerizing factor (ADF) gene family, which is conserved in eukaryotes, is important for plant development, growth, and stress responses. Cold stress restricts wheat growth, development, and distribution. However, genome-wide identification and functional analysis of the ADF family in wheat is limited. Further, because of the promising role of ADF genes in cold response, there is need for an understanding of the function of this family on wheat under cold stress. In this study, 25 ADF genes (TaADFs) were identified in the wheat genome and they are distributed on 15 chromosomes. The TaADF gene structures, duplication events, encoded conversed motifs, and cis-acting elements were investigated. Expression profiles derived from RNA-seq data and real-time quantitative PCR analysis revealed the tissue- and temporal-specific TaADF expression patterns. In addition, the expression levels of TaADF13/16/17/18/20/21/22 were significantly affected by cold acclimation or freezing conditions. Overexpression of TaADF16 increased the freezing tolerance of transgenic Arabidopsis, possibly because of enhanced ROS scavenging and changes to the osmotic regulation in cells. The expression levels of seven cold-responsive genes were up-regulated in the transgenic Arabidopsis plants, regardless of whether the plants were exposed to low temperature. These findings provide fundamental information about the wheat ADF genes and may help to elucidate the regulatory effects of the encoded proteins on plant development and responses to low-temperature stress.